2010
DOI: 10.1007/s12206-009-1146-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the ink transfer mechanism in R2R application

Abstract: Ink transfer process from the printing roll to the web was investigated using a Computational Fluid Dynamics (CFD) technique for the roll-to-roll (R2R) printing application. A parametric study was conducted to identify the effects of fluid parameters such as viscosity, surface tension and contact angle. To make the present analysis more relevant to the real printing system, a three-dimensional computational configuration for the commercial software was set up using the information obtained from the typical R2R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
3
14
0
1
Order By: Relevance
“…The presence of reduced viscosity, in turn, is thought to lead to the occurrence of a reduced line width in the calculation as well as in the observed discontinuity of the measurement data shown in Figure 9. In fact, the improvement obtained through the Carreau model seems to be reasonable considering our previous results under the Newtonian assumption, [17][18][19] which shows that the characteristics of the ink transfer process significantly vary with the magnitude of the viscosity. Since the simulation results with these two different cavity shapes compared favorably with the measurement data, it was assumed that the present numerical methodology with the Carreau model was reasonably able to capture important physical features of the ink transfer process.…”
Section: Validation Of the Numerical Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The presence of reduced viscosity, in turn, is thought to lead to the occurrence of a reduced line width in the calculation as well as in the observed discontinuity of the measurement data shown in Figure 9. In fact, the improvement obtained through the Carreau model seems to be reasonable considering our previous results under the Newtonian assumption, [17][18][19] which shows that the characteristics of the ink transfer process significantly vary with the magnitude of the viscosity. Since the simulation results with these two different cavity shapes compared favorably with the measurement data, it was assumed that the present numerical methodology with the Carreau model was reasonably able to capture important physical features of the ink transfer process.…”
Section: Validation Of the Numerical Resultssupporting
confidence: 87%
“…Noting our earlier results, [17][18][19] which primarily showed that a larger viscosity tends to produce better quality in terms of the transferred ink shape and that the contact angle played a much less significant role than the viscosity, one of the most effective ways of improving the printing quality has to do with controlling the fluid properties at the step of ink formulation instead of modifying the pattern shape. Another obstacle for complete analysis is the complication resulting from the tension and elasticity of the web: deflection of the web may cause unexpected defects in the case of very thin lines.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations